KEANEKARAGAMAN JENIS ANGGREK DI BEBERAPA KETINGGIAN TEMPAT DI KAWASAN TAMAN NASIONAL LORE LINDU DI DESA KARUNIA KECAMATAN PALOLO KABUPATEN SIGI - Zein, Moh.; Mallombasang, Sri Ningsih; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2019)
Sulawesi is the largest island in the central Wallacea region, so Sulawesi has a high level of diversity, both flora and fauna. Forest products are divided into two forest products consisting of wood and non-wood, one of the non-wood forest products is the orchid plant. (Pasimbong, 2013). Natural orchids are a group of plants that have not received much attention, in Sulawesi where information and publications on these various orchids have not been abundant. This study was conducted to determine the type of orchid at several altitudes in the Lore lindu National Park area in Karunia Village, Palolo District, Sigi Regency. This research will be conducted from April to June 2017, located in the Lore Lindu National Park area in Karunia Village, Palolo District, Sigi Regency. The study was conducted using the method of Identification of the diversity of orchid species at several altitudes in the forest area of the recipient village. The determination of the sampling was done intentionally (purposive sampling), each plot was taken at the location and provided for access (access). The results showed facts of orchid species in Karunia Village. There were 18 species found in the study sites in four areas of the Lore Lindu National Park Area in Karunia Village, Palolo Subdistrict, Sigi Regency. The highest value is based on 2,756 and the one with the highest H 'value is Spathoglotis plicata, with a value of H' = 0.2581. Send the lowest species variation index in the Dendrobium sp 4 orchid species with H '= 0.0910. Orchid species in Karunia Village are categorized as medium.Keywords: Diversity, Orchids, Gifts, Lore Lindu National Park.